Macrophage mannose receptor, CD206, predict prognosis in patients with pulmonary tuberculosis - Suzuki, Yuzo (Sci Rep, 2018)
Tuberculosis (TB) remains a leading cause of fatal infectious disease. Accumulations of macrophages are found in infected sites; thus, we hypothesized that a marker of activated macrophages may be related to prognosis of pulmonary TB (PTB). This study investigated serum soluble macrophage mannose receptor, sCD206, in PTB and examined its clinical significance. First, the concentration of sCD206 was measured in the sera of 96 patients with PTB (Tenryu cohort), and in pleural effusions from 29 patients with TB pleurisy. These were verified in another independent cohort (Shizuoka cohort). We found increased concentrations of sCD206 in sera, but not in pleural effusions of PTB patients. Notably, PTB patients with poor prognosis showed significantly higher levels of serum sCD206. At a cut-off value of 1,600 ng/mL in the Tenryu cohort, sCD206 predicted prognosis of PTB with area under the curve 0.847, sensitivity 77.3%, and specificity 86.5%. These results were validated in the Shizuoka cohort. Pathological analyses showed concordance of enhanced CD206 expression in lung and pleural tissues with caseating granuloma in TB. Serum sCD206 increased in PTB and was associated with prognosis. sCD206 is a potential biomarker for PTB.